MoTe2 : semiconductor or semimetal? - Deng, Ya (2022)
Transition metal tellurides (TMTs) have attracted intense interest due to their intriguing physical properties arising from their diverse phase topologies. To date, a wide range of physical properties have been discovered for TMTs, including that they can act as topological insulators, semiconductors, Weyl semimetals, and superconductors. Among the TMT families, MoTe2 is a representative material because of its Janus nature and rich phases. In this Perspective, we first introduce phase structures in monolayer and bulk MoTe2 and then summarize MoTe2 synthesis strategies. We highlight recent advances of Janus MoTe2 in terms of material structures and emerging quantum states. We also provide insight into the opportunities and challenges faced by MoTe2-associated device design and applications.